Major clinical relevance and considerations of zygomatic implants in elderly patients: a systematic review - Morais, Gabriella (2024)
For decades, zygomatic implants (ZI) have been used to rehabilitate atrophic maxillae and reconstruct maxillary defects, demonstrating significant survival rates, and have emerged as an alternative to extensive bone grafting. Despite their efficacy, surgical techniques for ZI placement have consistently been associated with perioperative complications, with additional problems arising later, especially in elderly patients. Objective: The present study developed a systematic review to address the main clinical relevance and considerations of zygomatic implants in elderly patients. Methods: The present study followed a concise systematic review model. The search was carried out in the PubMed, Embase, Ovid, Cochrane Library, Web of Science, and Scopus databases. The quality of the studies was based on the GRADE instrument and the risk of bias was analyzed according to the Cochrane instrument. Results and Conclusion: A total of 220 articles were found. In total, 77 articles were fully evaluated and 57 were included and evaluated in this study, and of the total of 57 articles, only 42 articles were developed in the item results of the systematic review. Of the initial total of articles, 108 articles were excluded because they did not meet the GRADE and AMSTAR-2 classification, and 20 were excluded because they presented a risk of bias that could compromise the credibility of the studies. The symmetric funnel plot does not suggest a risk of bias. According to the GRADE instrument, most studies presented homogeneity in their results, with X2=85.6%>50%. It was concluded the ZI has a high rate of survival accumulated in 12 years, with the majority of failures occurring in the early stages of the postoperative period. The main complication observed related to zygomatic implants in elderly patients was sinusitis, which can appear several years after implantation surgery. The presence of increased maxillary sinus pneumatization with advanced resorption of the posterior alveolus may result in insufficient bone to anchor the implant. Bone augmentation is generally necessary under these conditions to allow the placement of a sufficient number and length of implants. Another more serious condition would be defects of maxillectomy, aplasia of the maxillary sinus, and cleft deformities. Zygomatic implants appear to be a consolidated therapeutic option for a significantly atrophic maxilla in elderly patients, offering a promising alternative to costly heavy bone graft techniques, fewer complications, less time for rehabilitation, less required prosthodontic work, and significantly higher survival rates.